Angka Partisipasi Kasar (APK) Anak Usia Dini di Sulawesi Tengah - Latief, Juraid Abdul; ., Amrullah; Awalunisah, Sita (Bomba: Jurnal Pembangunan Daerah, 2019)
This paper aims to discuss how the gross participation of early childhood education in Central Sulawesi. The writing method used is conceptual in nature which is sourced from books, news, other reading material and observations that are related to the government's efforts in developing early childhood education in Central Sulawesi. The government's efforts in participating in improving early childhood education in 2011-2017 are very significant. In 2011, the Rough Participation Rate was still 42.82%, 2012 rose to 55.12%, 2013 to 63.20%, then 2014 rose again to 76.41%, then 2015 has reached 85.41% and 2016-2017 has reached 88.12%. Furthermore, it can be seen in the data of the ministry of education and culture of the secretariat general of the education and cultural data and statistics centers in 2018 and 2019, Central Sulawesi has achieved a gross participation rate in the Ministry of Education and Culture Early Childhood Education 32.41 while the Ministry of Education and Culture is added by the Ministry of Religion 34.14. From these figures it can be seen that Central Sulawesi's Early Childhood Rough Participation Rate has declined over the past 2 years. But the Central Sulawesi government continues to strive to increase the development of Early Childhood Education in Central Sulawesi. Keywords: Participation Rough Early Childhoood Education, Early Childhood Education Central Sulawesi